Pengaruh Pendidikan Kesehatan Terhadap Perilaku Melakukan Sadari Pada Wanita Usia Subur: Literature Review - Solehati, Tetti; Mahmuudah, Lu'lu N; Pratiwi, Rery Yuliani; Fikri, Auliya Ramanda; Putri, Sarah Rauzana; Elhaqqa, Arina; Miliarta, Evita R; Ardliana, Ratna R; Eldiana, Liesta; Indriana, Vivi V; Supriadi, Supriadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Introduction: Breast cancer is a malignant disease in women where the mortality rate of sufferers increases every year. The importance of early detection steps to help women overcome these problems, one of them by doing breast self-examination (Breast Self-Examination) Behavior of a person to do breast self-examination is basically different, this is influenced by several factors, one of which is knowledge. Objective: This literature review aims to determine the effect of health education on the behavior of women of childbearing age in conducting BSE actions. Methods: Search for articles using an electronic database that is google schoolar, Science Direct, and Pubmed. Keywords used in Indonesian and English are